The dependence of the number of shots and rebounds on the change of rules in the top Czech Basketball Men League: A pilot study - Hrusa, P. (Journal of Human Sport & Exercise, 2015)
The research study focused on the dependence of shooting and rebounds on the change of basketball rules that came into effect at the beginning of the season 2014-15. A substantial rule change concerned the offensive rebound. When the team, that controls the ball and shoots on the basket, so that the ball touches the ring, goes on in the offence, this team has only 14 seconds for shooting to go (before the change there was 24 seconds). The aim of the pilot study was to verify the assumption that the rule change will be reflected in a higher number of total shots (2-point and 3-point) and total rebounds (offensive and defensive), and lower total successfulness of shots. The study focused on 2 consecutive seasons. The research sample comprised the total of 256 matches, 128 in the season 2013-14 and 128 in the current season 2014-15. The employed indicators were average values of number of shots and rebounds. Data were collected from official technical score sheets, recorded in the given seasons. Data evaluation was based on both quantitative and qualitative analysis and the results did not support the hypothesis that the basketball rule change would be reflected in a higher number of shots and rebounds. With regard to the fact that this is a pilot study, further research should follow and the findings are to be compared with the data after the end of the current season.